PERBANDINGAN HUKUM PAJAK DAN ZAKAT MENURUT SYARIAH DAN NEGARA - Fatmawati Zahroh; Harkaneri Harkaneri (J-MACC, 2020)
ABSTRACT This article describes how to compare tax and zakat law from the perspective of sharia (Islamic law) and state (positive law). There are many similarities and differences between this tax and zakat, in terms of both collectors and collectors. According to article 1 of the 2009 KUP Law on taxes and Law No. 23 of 2011 concerning zakat and its management. This article uses the literature study method to compare and describe existing legislation as well as some differences between tax and zakat. With the results and discussion that actually this tax and zakat if synergized will become two very large state revenues so that they can finance state expenditures, but this state expenditure will be divided into routine expenditures and expenditures for people who are unable to meet the obligations of a muzakki (compulsory zakat) to mustahik (recipient of zakat). If synergized like that, the amil zakat and the government must be observant in differentiating these expenditures to be channeled to those who are entitled to and expenditures as appropriate for the State Budget.